Perception of family farmers on the socio-environmental impacts caused by Açu Port in São João da Barra, Rio de Janeiro, Brazil - Pontes da Silva Júnior, José Luiz; Pedlowski, Marcos Antonio (Sociedade & Natureza, 2022)
Ground was first broken in 2007 for the Açu Port, one of the largest port projects in the state of Rio de Janeiro, in the Fifth District of São João da Barra. Construction of its megastructures involved the clearing of extensive areas of restinga and the execution of a broad process of family-owned farmland expropriation by the Rio de Janeiro government. The objective of this study is to evaluate local family farmers’ perceptions of change as a means to understand their interrelationship with the environment before and after the installation of the Açu Port. Data was collected using a semi-structured questionnaire that was designed to identify the positive and negative interventions related to the Açu Port in the Fifth District and local family farming systems. Two locations were selected for the sampling: Água Preta and Mato Escuro. Questionnaires were applied between May and August 2019 and a total of 105 farmers (65 in Água Preta and 40 in Mato Escuro) were enrolled in the study. The results show that local farmers believed the installation of the Açu Port directly interfered in their social, economic and environmental well-being. The main environmental and economic impacts listed by the farmers were: salinization of water used for irrigation of their plantations and the process of expropriation of their lands. The results obtained demonstrate that in addition to affecting the dynamics of São João da Barra coastal ecosystems, including the restinga and lagoons, the economic development model adopted by the Açu Port has affected the quality of life of these farmers, interfered with their agricultural areas and directly affected their social reproduction.